Creating path entanglement and violating Bell inequalities by independent photon sources - Wiegner, Ralph; Thiel, Christoph; von Zanthier, Joachim; Agarwal, G. S. (Physics Letters A, 2010)
We demonstrate a novel approach of violating position-dependent Bell inequalities by photons emitted via independent single photon sources in free space. We trace this violation back to path entanglement created a posteriori by the selection of modes clue to the process of detection. (C) 2010 Elsevier B.V. All rights reserved.

Dicke superradiance and hanbury brown and twiss intensity interference: Two sides of the same coin - Wiegner, Ralph; Oppel, Steffen; Bhatti, Daniel; Agarwal, Girish S.; von Zanthier, Joachim (Optics InfoBase Conference Papers, 2017)
We show that Hanbury Brown and Twiss intensity interference and Dicke superradiance can be considered as two sides of the same coin, resulting from multi-photon interferences appearing in higher order photon correlations.
CRIS-Team Scopus Importer:2023-03-27

Directional Superradiant Emission from Statistically Independent Incoherent Nonclassical and Classical Sources - Oppel, Steffen; Wiegner, Ralph; Agarwal, Girish Saran; von Zanthier, Joachim (Physical Review Letters, 2014)
Superradiance has been an outstanding problem in quantum optics since Dicke introduced the concept of enhanced directional spontaneous emission by an ensemble of identical two-level atoms. The effect is based on the correlated collective Dicke states which turn out to be highly entangled. Here we show that enhanced directional emission of spontaneous radiation can be produced also with statistically independent incoherent sources, via the measurement of higher-order correlation functions of the emitted radiation. Our analysis is applicable to a wide variety of quantum emitters, like trapped atoms, ions, quantum dots, or nitrogen-vacancy centers, and is also valid for incoherent classical emitters. This is experimentally confirmed with up to eight statistically independent thermal light sources. The arrangement to measure the higher-order correlation functions corresponds to a generalized Hanbury Brown-Twiss setup, demonstrating that the two phenomena, superradiance and the Hanbury Brown-Twiss effect, stem from the same interference phenomeno

Hong–Ou–Mandel interference without beam splitters - Mährlein, Simon; Oppel, Steffen; Wiegner, Ralph; von Zanthier, Joachim (Journal of Modern Optics, 2017)
We propose a new interferometric setup which displays a completely destructive generalized N-photon Hong–Ou–Mandel interference. The key property of this scheme is that it does not require any optical elements like beam splitters or integrated waveguide structures. The interference is intrinsically produced by the evolution of N photons in free space when emitted by N identical single photon sources and measured by N detectors in the far field. In this sense, the setup is a most simple and natural implementation of the Hong–Ou–Mandel interference effect, i.e. of a completely destructive multi-photon interference produced by independent incoherent sources.
Keywords: Higher-order intensity correlations; Hong–Ou–Mandel effect; Multi-photon interference

Nonlocality from N > 2 independent single-photon emitters - Thiel, Christoph; Wiegner, Ralph; von Zanthier, Joachim; Agarwal, G. S. (Physical Review A, 2010)
We demonstrate that intensity correlations of second order in the fluorescence light of N > 2 single-photon emitters may violate locality while the visibility of the signal remains below 1/root 2 approximate to 71%. For this, we derive a homogeneous Bell-Wigner-type inequality, which can be applied to a broad class of experimental setups. We trace the violation of this inequality back to path entanglement created by the process of detectio

Quantum interference and entanglement of photons that do not overlap in time - Wiegner, Ralph; Thiel, Christoph; von Zanthier, Joachim; Agarwal, G. S. (Optics Letters, 2011)
We discuss the possibility of quantum interferences and entanglement of photons that exist at different intervals of time, i.e., one photon being recorded before the other has been created. The corresponding two-photon correlation function is shown to violate Bell's inequalities. (c) 2011 Optical Society of America

Quantum interference and non-locality of independent photons from disparate sources - Wiegner, Ralph; von Zanthier, Joachim; Agarwal, G. S. (Journal of Physics B-Atomic Molecular and Optical Physics, 2011)
We quantitatively investigate the non-classicality and non-locality of a whole new class of mixed disparate quantum and semiquantum photon sources at the quantum-classical boundary. The latter include photon-added thermal and photon-added coherent sources, experimentally investigated recently by Zavatta et al (2009 Phys. Rev. Lett. 103 140406). The key quantity in our investigations is the visibility of the corresponding photon-photon correlation function. We present explicit results on the violations of the Cauchy-Schwarz inequality-which is a measure of non-classicality-as well as of Bell-type inequalitie

Quantum-interference-initiated superradiant and subradiant emission from entangled atoms - Wiegner, Ralph; von Zanthier, Joachim; Agarwal, G. S. (Physical Review A, 2011)
We calculate the radiative characteristics of emission from a system of entangled atoms which can have a relative distance larger than the emission wavelength. We develop a quantum multipath interference approach which explains both super-and subradiance though the entangled states have zero dipole moment. We derive a formula for the radiated intensity in terms of different interfering pathways. We further show how the interferences lead to directional emission from atoms prepared in symmetric W states. As a byproduct of our work we show how Dicke's classic result can be understood in terms of interfering pathways. In contrast to the previous works on ensembles of atoms, we focus on finite numbers of atoms prepared in well characterized state

Simulating Dicke-like superradiance with classical light sources - Bhatti, Daniel; Oppel, Steffen; Wiegner, Ralph; Agarwal, Girish; von Zanthier, Joachim (Physical Review A, 2016)
In this paper we investigate the close relationship between Dicke superradiance, originally predicted for an ensemble of two-level atoms in entangled states, and the Hanbury Brown and Twiss effect, initially established in astronomy to determine the dimensions of classical light sources such as stars. By studying the state evolution of the fields produced by classical sources-defined by a positive Glauber-Sudarshan P function-when recording intensity correlations of higher order in a generalized Hanbury Brown and Twiss setup we find that the angular distribution of the last detected photon, apart from an offset, is identical to the superradiant emission pattern generated by an ensemble of two-level atoms in entangled symmetric Dicke states. We show that the phenomenon derives from projective measurements induced by the measurement of photons in the far field of the sources and the permutative superposition of quantum paths identical to those leading to superradiance in the case of single photon emitters. We thus point out an important similarity between classical sources and quantum emitters upon detection of photons if the particular photon source remains unknown. We finally present a compact result for the characteristic functional which generates intensity correlations of arbitrary order for any kind of light sourc

Simulating superradiance from higher-order-intensity-correlation measurements: Single atoms - Wiegner, Ralph; Oppel, Steffen; Bhatti, Daniel; von Zanthier, Joachim; Agarwal, G. S. (Physical Review A, 2015)
Superradiance typically requires preparation of atoms in highly entangled multiparticle states, the so-called Dicke states. In this paper we discuss an alternative route where we prepare such states from initially uncorrelated atoms by a measurement process. By measuring higher-order intensity-intensity correlations we demonstrate that we can simulate the emission characteristics of Dicke superradiance by starting with atoms in the fully excited state. We describe the essence of the scheme by first investigating two excited atoms. Here we demonstrate how via Hanbury Brown and Twiss type of measurements we can produce Dicke superradiance and subradiance displayed commonly with two atoms in the single excited symmetric and antisymmetric Dicke states, respectively. We thereafter generalize the scheme to arbitrary numbers of atoms and detectors, and explain in detail the mechanism which leads to this result. The approach shows that the Hanbury Brown and Twiss type of intensity interference and the phenomenon of Dicke superradiance can be regarded as two sides of the same coin. We also present a compact result for the characteristic functional which generates all order intensity-intensity correlation

Versatile source of polarization-entangled photons - Maser, Andreas; Wiegner, Ralph; Schilling, Uwe; Thiel, Christoph; von Zanthier, Joachim (Physical Review A, 2010)
We propose a method for the generation of a large variety of entangled states, encoded in the polarization degrees of freedom of N photons, within the same experimental setup. Starting with uncorrelated photons, emitted from N arbitrary single-photon sources, and using linear optical tools only, we demonstrate the creation of all symmetric states (e. g., GHZ and W states), as well as all symmetric and nonsymmetric total angular momentum eigenstates of the N-qubit compoun